(untitled) (Educational Dimension, 2023)
This research aims to develop a methodology for utilizing cloud-based technologies in the teaching of higher mathematics. The study tasks involve identifying the features of mobile mathematical environments as tools for cloud-based technologies, developing a mobile mathematical environment specifically designed to support mathematics learning for students in economic disciplines, and formulating a methodology for employing the mobile mathematical environment. The research focuses on the process of teaching higher mathematics to students in economic disciplines. The subject of investigation encompasses the use of cloud-based learning technologies in the teaching of higher mathematics. The research methods employed include studying, summarizing, and systematizing scientific, methodological, and psycho-pedagogical literature; analyzing current educational standards and curricula; conducting targeted pedagogical observations, testing, and surveys; and analyzing the experience of using cloud-based learning technologies in the teaching of higher mathematics. The findings analyze the main features of mobile mathematical environments as tools for cloud-based technologies. The ``Higher Mathematics’’ mobile mathematical environment, designed to support the learning of higher mathematics for students in economic disciplines, is examined. Elements of the methodology for utilizing the ``Higher Mathematics’’ mobile mathematical environment in the teaching of higher mathematics are identified. The study identifies instructional formats through which the implementation of the ``Higher Mathematics’’ mobile mathematical environment occurs in the teaching of higher mathematics. The main conclusions and recommendations emphasize that the use of the ``Higher Mathematics’’ mobile mathematical environment in the teaching of higher mathematics enables students to master the necessary educational material and contributes to the development of cognitive activity, the formation of independent work skills, and the consolidation and systematization of knowledge.